Tropical geomorphology - Gupta, Avijit (Cambridge : Cambridge University Press, 2011)
'Although similar geomorphic processes take place in other regions, in the tropics these processes operate at different rates and with varying intensities. Tropical geomorphology therefore provides many new discoveries regarding geomorphic processes. This textbook describes both the humid and arid tropics. It provides thoroughly up-to-date concepts and relevant case studies, and emphasises the importance of geomorphology in the management and sustainable development of the tropical environment, including climate change scenarios. The text is supported by a large number of illustrations, including satellite images. Student exercises accompany each chapter. Tropical Geomorphology is an ideal textbook for any course on tropical geomorphology or the tropical environment, and is also invaluable as a reference text for researchers and environmental managers in the tropics'--
Includes bibliographical references (p. 349-373) and index.
Keywords: Geomorphology -- Tropics